Socioeconomic and Parental Determinants of Adolescent Pregnancy: A Cross-Sectional Study at Pekauman Community Health Center, Banjarmasin - Aditya, Renny (Indonesian Socety of Obstetrics and Gynecology, 2025)
Objective:This study examined the relationship between parental economic status, parental role, and the incidence of teenage pregnancy among adolescents at the Pekauman Community Health Center in Banjarmasin. Methods:An observational, cross-sectional analytic study was conducted with 50 randomly selected respondents. Data collection utilized validated questionnaires and in-depth interviews. Independent variables included education level, economic status, parental role, and reproductive health knowledge. Data analysis was performed using chi-square tests at a significance level of ? = 0.05 (SPSS, IBM). Results:Adolescent pregnancy was found to be significantly associated with low reproductive health knowledge (p = 0.0219; OR = 0.16), low economic status (p = 0.0008; OR = 10.40), low education level (p < 0.0001; OR = 19.43), and inadequate parental role (p = 0.034; OR = 4.0). The majority of adolescent mothers were under 18 years of age and had not completed high school. Health complications were prevalent, with 32% of adolescent mothers experiencing anemia. Conclusion:Adolescent pregnancy is primarily influenced by inadequate reproductive health knowledge, low educational attainment, economic hardship, and insufficient parental support. Comprehensive strategies are required, including reproductive health education, socioeconomic empowerment, and active parental engagement. These interventions are essential for reducing adolescent pregnancy rates and improving maternal and child health outcomes. Local health authorities should prioritize community-based reproductive health education programs that involve both adolescents and their parents to facilitate accurate knowledge dissemination and open communication. Keywords:Adolescent pregnancy, parental role, reproductive health knowledge, socioeconomic status.